SCREENCAST DEVELOPMENT IN BIOLOGY ON FLIP CLASSROOM - Puspaningsih, Ayu Ratna (Universitas Pendidikan Ganesha, 2018)
The implementation of flipped classroom at SMA Negeri Bali Mandara (Senior high School) helped to accommodate semesteral-credit-system or SKS and to benefit from the e-learning system. However, students’s achievement in Biology lesson was still 2 points below the school’s passing grade (KKM) due to the inefectivity and the lack of interactivity of the learning media used. To counter this challenge therefore, video screencast was developed. This R & D project aims at: 1) to create a suitable screencast video which supporting student’s learning, 2) to investigate the effecivity of the prototype, 3) to know the student’s responses the use of screencast video to support their learning. Prototype was developed by using 4-D steps, which are: define, design, development and dissemination. The prototype was then validated by content and media experts. The product was lauched and implemented for students in Grade 12 and 10. Data response were collected by using questionnaire and finally were analysed both qualitatively and quantitatively. Students’s responses were positive which supported by the fact that the use of screencast video during flipped learning improved their learning achievement